2018
DOI: 10.7567/jjap.57.11uc04
|View full text |Cite
|
Sign up to set email alerts
|

Insulation resistance degradation mechanisms of multilayer ceramic capacitors during highly accelerated temperature and humidity stress tests

Abstract: The failure mechanisms of multilayer ceramic capacitors (MLCCs) with Ni internal electrodes under high temperature and high voltage conditions have been investigated through highly accelerated life tests (HALTs) in recent years. Generally, insulation resistance degradation during HALTs is presumed to be because of the electromigration of oxygen vacancies. Reliability in high-temperature, high-humidity, and rated-voltage environments is important for MLCCs. However, only a few studies have investigated the caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Consequently, the leakage current increases as the protons diffuse into the dielectric. 23) It was verified that water vapor infiltrates the MLCC 24) using deuterium, as a tracer. It was observed, that deuterium was biased toward the cathode-side inner electrode in the BaTiO 3 -based dielectric exhibiting increased leakage current.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Consequently, the leakage current increases as the protons diffuse into the dielectric. 23) It was verified that water vapor infiltrates the MLCC 24) using deuterium, as a tracer. It was observed, that deuterium was biased toward the cathode-side inner electrode in the BaTiO 3 -based dielectric exhibiting increased leakage current.…”
mentioning
confidence: 92%
“…In previous studies, it was presumed that when water vapor infiltrated the interface between the anode-side inner electrode and the dielectric, electrolysis occurred at the interface, as shown in the equation below, and D + was attracted to the cathode-side inner electrode by migration through the dielectric. [23][24][25] Considering the results of Fig. 3(a) and the aforementioned presumption, the deuterium in the dielectric is presumed to exist as D +…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28] Recently, Saito et al reported the failure mechanisms of MLCCs during HASTs. 29) It is presumed that infiltration of water vapor into MLCCs generates hydrogen ions via electrolysis of H 2 O at the interface of the ceramics and the internal electrodes on the anode side; thereafter, these hydrogen ions, which diffuse to the dielectrics, cause an increase in the leakage current. 29) However, this does not show that the increase in the leakage current of MLCCs is directly linked to water vapor infiltration; thus, in this study, to verify this idea, we investigated whether the water vapor that infiltrated the MLCCs caused an increase in the leakage current.…”
mentioning
confidence: 99%
“…These MLCCs had a chip size of 3.2 mm × 1.6 mm × 1.6 mm, a capacitance of 10 μF, a rated voltage of 16 V, a dielectric layer thickness of 3 μm, a Ni internal electrode layer with a thickness of 1 μm and 340 dielectric layers. Based on previous studies, 29) the thickness of the external electrode of these MLCCs was one-quarter of the conventional MLCC thickness; this facilitates the infiltration of water vapor into the MLCCs. The MLCCs were used as test chips.…”
mentioning
confidence: 99%